In Vivo Bioactivities of Hoya parasitica (Wall.) and In Silico Study against Cyclooxygenase Enzymes. (28th April 2022) - Sarkar, Kishore Kumar; Mitra, Trina; Rahman, Md Asibur; Raja, Iqbal Mahmud; Aktaruzzaman, Md; Abid, Md Ahsan; Zilani, Md Nazmul Hasan; Roy, Debendra Nath
Abstract : Hoya parasitica (Wall.) is extensively used in traditional medicine for the treatment of various diseases including rheumatism, kidney problems, jaundice, urinary tract disorders, fever, and pain. The present study was designed to explore new lead compound(s) to alleviate pain, pyresis, and diarrhea from methanol, ethyl acetate, and n-hexane extracts of H. parasitica (Wall.) leaves (MHP, EAHP, and NHP, respectively). Analgesic activity of the extracts was assessed through acetic acid induced writhing, tail immersion, and hot plate tests while brewer's yeast-induced pyrexia test was employed for the assessment of antipyretic activity. Besides, castor oil and magnesium sulfate induced diarrheal tests were utilized for the evaluation of antidiarrheal properties. Moreover, in silico study of the isolated compounds was undertaken to seek out best-fit phytoconstituent(s) against cyclooxygenase enzymes. MHP revealed substantial antioxidant activities in different in vitro assays compared to EAHP and NHP. In the acetic acid-induced writhing test, among the extracts, MHP (400 mg/kg) revealed maximum 74.15 ± 1% inhibition of writhing comparable to that of standard (85.77 ± 1.39%). Again, in tail immersion and hot plate tests, higher doses of all the test samples exhibited a significant increase of latent period in a time-dependent manner. In brewer yeast-induced pyrexia test, at 3 rd and 4 th hour of treatment, significant (P < 0.05 ) antipyretic action was found in the test samples. In both castor oil and magnesium induced diarrheal tests, MHP at 400 mg/kg showed the highest percent inhibition of diarrhea (68.62 ± 4.74 and 64.99 ± 2.90, respectively). Moreover, molecular docking analysis corroborated the results of the present study. The findings of the present study supported the traditional uses of this plant for the alleviation of pain and fever. Furthermore, hoyasterone was found to be the most effective lead compound as cyclooxygenase enzyme inhibitor.